2016
DOI: 10.1007/s00402-016-2486-9
|View full text |Cite
|
Sign up to set email alerts
|

A treatment strategy for proximal femoral benign bone lesions in children and recommended surgical procedures: retrospective analysis of 62 patients

Abstract: This treatment strategy can provide good local control and excellent functional and radiological results in the management of benign bone lesions of the proximal femur in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 34 publications
0
41
1
Order By: Relevance
“…However, our fixation strategy might be insufficient in all circumstances as up to 10 times a person’s body weight can be exerted on the hips during running or intense activities ( Çaypınar et al, 2016 ). Previous clinical studies also reported that no periprosthetic fracture was reported at either 6 months ( Singh et al, 2015 ) or 48 months ( Erol et al, 2016 ) after local curettage and prophylactic fixation using two cannulated screws in benign femoral neck lesion adult patients, with a restriction of intense activities before bone healing. Overall, we suggested that the application of two cannulated screws for prophylactic fixation is feasible for an aggressive benign femoral neck lesion in adult patients, even with an entire anterior cortical bone defect.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…However, our fixation strategy might be insufficient in all circumstances as up to 10 times a person’s body weight can be exerted on the hips during running or intense activities ( Çaypınar et al, 2016 ). Previous clinical studies also reported that no periprosthetic fracture was reported at either 6 months ( Singh et al, 2015 ) or 48 months ( Erol et al, 2016 ) after local curettage and prophylactic fixation using two cannulated screws in benign femoral neck lesion adult patients, with a restriction of intense activities before bone healing. Overall, we suggested that the application of two cannulated screws for prophylactic fixation is feasible for an aggressive benign femoral neck lesion in adult patients, even with an entire anterior cortical bone defect.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, prophylactic internal fixation is currently preferred for aggressive benign femoral neck lesions in adults ( Nakamura et al, 2015 ; Panchwagh et al, 2018 ). Several options of the internal implant for an aggressive benign femoral neck lesion were previously reported, including cannulated screws ( Singh et al, 2015 ; Erol et al, 2016 ), intramedullary fixation ( Zhang et al, 2017 ), and compression hip screw ( Nakamura et al, 2015 ). However, there is still no agreed consensus on the optimal selection of the internal fixation implant which provides not only sufficient biomechanical strength but also a minimally invasive approach after curettage ( Shi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies on benign bone lesions in pediatric populations are limited because of a lack of understanding of the natural history of benign bone disorders[ 12 ]. Many surgeons treat these patients surgically in the light of personal experience, individual radiographic criteria, or some combination[ 3 , 13 ]. In our study, we present a modified scoring method predicting the risk of pathological fracture in pediatric patients based on four variables as scoring parameters.…”
Section: Discussionmentioning
confidence: 99%
“…When an enlarging benign lesion occurs in the long bone of the extremities, pathologic fracture may occur frequently even with minimal trauma. Pathologic fracture will lead to fracture-related pain, deformity, and immobility[ 3 ]. Therefore, fracture prevention is a management priority[ 4 ].…”
Section: Introductionmentioning
confidence: 99%